ANALISIS PETA SEBARAN KUALITAS AIR DI KECAMATAN PONTIANAK BARAT KOTA PONTIANAK PROVINSI KALIMANTAN BARAT - Syahwanti, Hezliana; Widodo, Muji Listyo; Christiana, Ranty; Putri, Ivo Dwi; Maulina, Syf. Melly (Politeknik Negeri Semarang, 2024)
The city of Pontianak has the longest river in West Kalimantan, namely the Kapuas River. This river is used by the majority of Pontianak City residents in their daily activities, including the West Pontianak District area. As a result, river water quality can change over time. Many influencing factors, such as human activities, are thought to cause the lake's water quality to become low. One way to control pollution in an ecosystem can be done by monitoring water quality over a certain period of time, so that the water quality status is known. Based on the description above, it is currently important to carry out an article regarding analysis of water quality distribution maps and water quality status in the West Pontianak District area. This article aims to analyze the level of pollution and how widespread the water pollution is in the West Pontianak District, Pontianak City by carrying out mapping based on water quality data using a Geographic Information System (GIS). The results of this research are that on the 2019, 2020 and 2021 distribution maps, analysis was carried out for 7 parameters, namely BOD, COD, Nitrate, PH, Temperature, TDS and TSS values. These 7 parameters show mutually supporting results that based on the distribution map, it can be seen that the water quality in the West Pontianak District area still seems safe for people to use for their daily activities. Even the Nitrate, PH, Temperature, TDS and TSS values appear to have increased from 2019 to 2021. This shows better water quality than the previous year. In 2020 and 2021 there are 2 additional parameters, namely DO and Phosphate and in 2021 there is a fecal coliform parameter. These three additional parameters also support the results of the previous 7 parameters. It can be seen that good changes have occurred in the water quality in the West Pontianak District area. The DO and phosphate distribution map show changes in values from 2020 and 2021, which shows that the water quality in the area is getting better. The fecal coliform distribution map shows that only a few points are contaminated with the feces of living creatures.